Promoter mutations that allow nifA-independent expression of the nitrogen fixation nifHDKY operon. - Bitoun, R (1983)
The nifHDKY operon of Klebsiella pneumoniae encodes for structural polypeptides of nitrogenase and requires the nifA gene product for transcription. Mutations that allow transcription of the nifHDKY operon in absence of the nifA gene product were characterized in plasmids containing the regulatory region of nifHDKY and nifH fused in phase to lacZ. beta-Galactosidase activity served as a measure for nifH expression. Most mutations were located in the nif regulatory region and included insertion sequence 2 (IS2) insertions, a sequence duplication, and a base substitution. In Escherichia coli, beta-galactosidase activity expressed from the mutant plasmids in the absence of nifA was 6-30% of the nifA-activated, parental level. Expression from most mutant plasmids was further increased by nifA. In K. pneumoniae, IS2-containing plasmids expressed low levels of beta-galactosidase and responded poorly, if at all, to activation by nifA, whereas expression from other mutant types was similar to that observed in E. coli. Nucleotide sequence analysis of two mutants indicated that sequences within 41 base pairs upstream to the nifH coding sequence were involved in nif-specific regulation. The results suggest that an inverted repeat element in this region, which could theoretically form a cruciform structure in the DNA, is involved in the transcriptional control of the nifHDKY operon.